Childhood Asthma and its Associated Factors Among Children Attending a Tertiary Level Hospital Kathmandu - Lamichhane, Narayani; Upreti, Kamala; Shrestha, Saraswati; Pradhan, Mary; Bhandari, Bhagawati (Journal of Nepal Paediatric Society, 2022)
Introduction: Childhood asthma is one of the most common non-communicable chronic pulmonary diseases of children and causes considerable morbidity. Prevalence of childhood asthma has grown dramatically in developed as well as developing countries. The objective of the study was to find out the factors associated with childhood asthma among children attending Kanti Children’s Hospital, Kathmandu, Nepal. Methods: Descriptive, cross-sectional study design was adopted and 152 parents were selected by using non probability purposive sampling technique. Data was collected using pre tested structured with an interview schedule after permission from concerned authorities. The data was analyzed by using descriptive and inferential statistic with SPSS IBM 16. Results: The finding of the study revealed that various factors were associated with childhood asthma. Among child related factors, age of children 6 years and above (p-value = < 0.001, OR = 4.190, 95% CI: 1.814 - 9.678), absence of exclusive breast feeding (p-value = 0.021, OR = 2.14, 95% CI: 1.062 - 4.351), history of recurrent allergy and rhinitis (p-value 0.049, OR = 1.9117, 95% CI: .953 - 3.856) and influenza vaccine (p-value = 0.001, OR = 3.714 95% CI:1.691-8.157) and in maternal factors, history of asthma in mother (p-value = 0.002, OR = 13.662, 95% CI:1.729 - 107.994), and on environmental factors, presence of dampness at home (p-value = 0.001, OR = 3.7142, 95% CI: 1.5584 - 9.3408) were found to have significant association with childhood asthma. Conclusions: It could be concluded that 50.7% of children were diagnosed as asthma. Several factors were associated with childhood asthma. Children age 6 years and above, lack of exclusive breast feeding, history of recurrent allergy and rhinitis and presence of dampness at home, maternal history of asthma and seeking of influenza vaccine were found significant association with childhood asthma.